Patient with Ebstein anomaly and Down syndrome. Strange combination - Jesús de Rubens-Figueroa; Bruno Marino (Instituto Nacional de Pediatría, 2014)
The most common congenital heart diseases in children with Down syndrome are atrial or ventricular septal defects, patent ductus arteriosus or endocardial cushion defects.